2018
DOI: 10.1089/met.2017.0055
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Community-Based Lifestyle Intervention on Metabolic Syndrome and Its Components in Adolescents: Findings of a Decade Follow-Up

Abstract: The healthy lifestyle intervention reduced the risk of MetS in both genders in short and long term, but with different patterns and improved some of the MetS components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
2
10
0
8
Order By: Relevance
“…This finding emphasizes the need for ongoing support, long-term educational intervention to reduce fasting blood glucose level. Findings of the current study revealed that the three-month lifestyle intervention decreased the prevalence of MetS in both group, which are in line with Bright Bodies and other shortterm intervention studies [23,34,35].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding emphasizes the need for ongoing support, long-term educational intervention to reduce fasting blood glucose level. Findings of the current study revealed that the three-month lifestyle intervention decreased the prevalence of MetS in both group, which are in line with Bright Bodies and other shortterm intervention studies [23,34,35].…”
Section: Resultssupporting
confidence: 91%
“…The results of our study revealed that combination of different educational methods include face-toface education, pamphlet presentation, telephone text messaging, and educational films within 3 months were effective.Generally, the results of this study are consistent with Azizi and Amiri studies, which showed, healthy 6 lifestyle intervention reduce the risk of MetS in both genders in short term[16,23].A similar study from Thailand undertaken by Chaiyasoot et al showed that a 3 months' lifestyle educational intervention in adults with obesity and metabolic syndrome resulted in in significant reduction in weight, waist circumference, blood pressure, and lipid profile [24]. Our Findings reflects that lifestyle intervention has modest efficacy in reducing weight.…”
supporting
confidence: 90%
“…However, this effect was not maintained in the long run (wave 4 and wave 5) 37 . Moreover, our recent study in the adolescent participants of the TLGS, showed that the lifestyle intervention prevented metabolic syndrome in a short time (wave 2) but not in long-term (wave 4) 36 . There is limited evidence about the long-term effects of a community-wide lifestyle intervention program on the incidence of T2D or the prevalence of its risk factors.…”
Section: Discussionmentioning
confidence: 94%
“…Details of the lifestyle intervention have been reported previously 17 , 30 , 36 – 38 ; briefly, the lifestyle intervention design was adapted from the North Karelia project 39 , 40 and using American Heart Association guidelines. For this purpose, findings of the need assessments and Knowledge, Attitude, and Practice (KAP) studies in the TLGS communities were also used 41 , 42 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation